EXPLORING LANGUAGE ASSESSMENT LITERACY OF EFL TEACHERS IN THE CONTEXT OF INDONESIAN HIGHER EDUCATION - Andri Suherman (University of Kuningan, 2022)
The present study aims at examining EFL teachers’ perceptions of Language Assessment Literacy (hereafter LAL) in the context of Indonesian higher education. To this aim, purposive sampling technique was employed to select sixteen EFL university teachers to participate in an online questionnaire and semi-structured interviews. The finding showed that the participants had applied six types of LAL in their teaching practices with formative assessment methods and test validity and reliability being the two most applied (more than 80%) by the participants. Following this, between 75% and 80% participants had applied two other types of LAL, linguistics competence and test results. The last two types of LAL, digital literacy and grading criteria, were applied by less than 70% participants. Another finding from qualitative data revealed that the majority of participants (over 70%) ranked their level of LAL knowledge and skills as low. Despite some limitations, the present study provides some implications including the necessity for the EFL teachers to be equipped with relevant knowledge and skills to make the way for quality assessment. It is therefore university authorities should organize professional development programs with the purpose to help teachers improve their assessment literacy. In addition, all educational parties should collaborate to consistently conduct literacy assessment projects throughout teachers’ professional career. Some suggestions for future research in the field of language assessment are also presented.